PENGARUH KOMPETENSI, KARAKTERISTIK INDIVIDU DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING - Anggraenie, Roesalia; Dwiatmadja, Christantius; Santoso, Djoko (ITB AAS Indonesia Surakarta, 2024)
This research aims to analyze the influence of competency, individual characteristics, organizational culture, and motivation on job satisfaction, as well as analyze the influence of competency, individual characteristics, and Organizational Culture on Job Satisfaction with the intervening variable Motivation.This research method uses a type of research with a quantitative explanatory approach. The population and sample used were all Temanggung Regency Satpol PP and Fire Department contract employees, totaling 70 respondents. The sampling technique used was the census technique. Data analysis uses linear regression analysis by testing the t-test and Sobel test.The results of the analysis in this study show that the competency variable partially has a positive and insignificant effect on job satisfaction, the individual characteristic variable partially has an insignificant negative effect on job satisfaction, the organizational culture and motivation variables partially have a significant positive effect on job satisfaction, the influence of competence through motivation does not have a significant influence on job satisfaction and the influence of individual characteristics and organizational culture through motivation has a significant influence on job satisfaction.